ROLE OF EXERCISES IN FORMING CORRECT PRONUNCIATION SKILLS IN STUDENTS - Nargiza SALOMOVA (Scholar Express Journal, 2023)
This article is written about the role of exercises in the formation of correct pronunciation skills in students. We observe that the student has thoroughly studied the issue of literary pronunciation and its norms in the languages of the developed countries of the world. In this regard, phonetic exercises are used effectively in the world experience, including in English.
Keywords: student; pronunciation; exercise